2022
DOI: 10.1002/ana.26494
|View full text |Cite
|
Sign up to set email alerts
|

Transverse Myelitis Following SARS‐CoV‐2 Vaccination: A Pharmacoepidemiological Study in the World Health Organization's Database

Abstract: Background Transverse myelitis (TM) has recently been associated by health authorities with Ad26.COV2.S (Janssen/Johnson & Johnson), one of the 5 US Food and Drug Administration (FDA) or European Medicines Agency (EMA) labeled severe acute respiratory syndrome‐coronavirus 2 (SARS‐CoV‐2) vaccines. It is unknown whether a similar association exists for the other FDA or EMA labeled SARS‐CoV‐2 vaccines (BNT162b2 [Pfizer/BioNTech], mRNA‐1273 [Moderna], ChAdOx1nCov‐19 [Oxford–AstraZeneca], and NVX‐CoV23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…23 However, transverse myelitis had a later peak (late fall/winter) than other neuroinflammatory disorders, which may be due to cases of transverse myelitis associated with viral infections or vaccinations. 24,25 Despite a large and growing body of literature on seasonality in neurologic disease, direct comparisons between existing studies are challenging as they are conducted in different geographic areas using variable data sources and case ascertainment methods. By using a large, nationally representative database of inpatient hospitalizations in the United States, we are able to not only validate previous findings at a national level but also compare the relative magnitude of seasonal variation across different diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 However, transverse myelitis had a later peak (late fall/winter) than other neuroinflammatory disorders, which may be due to cases of transverse myelitis associated with viral infections or vaccinations. 24,25 Despite a large and growing body of literature on seasonality in neurologic disease, direct comparisons between existing studies are challenging as they are conducted in different geographic areas using variable data sources and case ascertainment methods. By using a large, nationally representative database of inpatient hospitalizations in the United States, we are able to not only validate previous findings at a national level but also compare the relative magnitude of seasonal variation across different diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Influenza vaccination has been associated with a transiently lower risk of multiple sclerosis exacerbation, so it is possible that this is true of other demyelinating diseases such as optic neuritis and neuromyelitis optica 23 . However, transverse myelitis had a later peak (late fall/winter) than other neuroinflammatory disorders, which may be due to cases of transverse myelitis associated with viral infections or vaccinations 24, 25 …”
Section: Discussionmentioning
confidence: 99%
“…Other inflammatory CNS conditions including autoimmune encephalitis have also been reported in temporal association with COVID-19 vaccines. Causality is uncertain, and the degree of risk beyond the background rate has been difficult to ascertain 88,94,95 …”
Section: Covid-19 Vaccine and Prevention Considerationsmentioning
confidence: 99%
“…Causality is uncertain, and the degree of risk beyond the background rate has been difficult to ascertain. 88,94,95 Guillain-Barré syndrome is often associated with preceding infections or vaccinations. Onset is typically within 6 weeks of vaccine exposure.…”
Section: Cerebrovascular Eventsmentioning
confidence: 99%
“…In a selection of studies on worsening of myasthenia in antibiotics, 10 antidepressants and neuroleptics, 17 QT prolongation in neuroleptics, 22 transverse myelitis after COVID-19 vaccination, 23 the 30 most frequent ADRs in edoxaban 24 and induction of PML by immunosuppressant drugs 9 there is a large range of expected ADR frequency. The error rates of the drugs in these studies as obtained from simulations with the respective values for P0 and N are shown in Figure 7 together with a simulation for the full range of ADR frequencies with P0 = 0.01 and N = 1 000 000 for expected case numbers below the position of peak n. Figure 3 shows that for n = 3 false positive rates of 0.05 are possible when in fact 0.025 was intended.…”
Section: Oscillations Of Sensitivity and False Positive Ratementioning
confidence: 99%